ISOLASI DAN KARAKTERISASI STRUKTUR FLAVONOID DARI TUMBUHAN SARIPATI (Clerodendron infortunatum Linn) - isniyetti, Isniyetti (Lembaga Penelitian Universitas Negeri Padang, 2009)
A flavonoid of the Clerodendron infortunatum Linn has been isolated by ethylacetate fraction of its methanolic extract. Apigenin (5,4 ,dihydroksiflavon) was isolated by chromatography over silica gel with ethylacetate – hexane as eluent and then crystallized from ethylacatate – hexane to give the flavonoid as plates, m..p. 289-291 0C. The structure of which followed from its spectroscopic properties. Key word : Flavonoid, elusidation, ethylacetate fraction, chromatografi, spectroscopic properties.